Preparation and Characterization of Cross-Linked Natural Rubber/Multi-Walled Carbon Nanotube/Clay Nanocomposites - Ghorbani, Mohammadreza (2011)
Polymer composites have a wide range of applications in electronics, transportation, construction and consuming products.In recent years, polymer/clay nanocomposites have been extensively studied due to improved properties of the material produced. In addition, polymer/nanotube nanocomposites have been given a special attention because of the unique properties of carbon nanotubes. One of the problems of using these fillers separately is the existence of their agglomerations. It was suggested to overcome this problem and also to obtain new properties of the products by using of two fillers.